Phytochemical Profiling, In Vitro Biological Activities, and In-Silico Studies of Ficus vasta Forssk.: An Unexplored Plant - Hanan Y. Aati; Mariyam Anwar; Jawaher Al-Qahtani; Areej Al-Taweel; Kashif-; Sultan Aati; Faisal Usman; Bilal Ahmad Ghalloo; Hafiz Muhammad Asif; Jafir Hussain Shirazi; Aliza Abbasi (MDPI AG, 2022)
Ficus vasta Forssk. (Moraceae family) is an important medicinal plant that has not been previously investigated for its phytochemical and biological potential. Phytochemical screening, total bioactive content, and GCMS analysis were used to determine its phytoconstituents profile. Antioxidant, antibacterial, antifungal, anti-viral, cytotoxicity, thrombolytic, and enzyme inhibition activities were examined for biological evaluation. The plant extract exhibited the maximum total phenolic (89.47 ± 3.21 mg GAE/g) and total flavonoid contents (129.2 ± 4.14 mg QE/g), which may be related to the higher antioxidant potential of the extract. The extract showed strong α-amylase (IC50 5 ± 0.21 µg/mL) and α-glucosidase inhibition activity (IC50 5 ± 0.32 µg/mL). Significant results were observed in the case of antibacterial, antifungal, and anti-viral activities. The F. vasta extract inhibited the growth of HepG2 cells in a dose-dependent manner. The GCMS analysis of the extract provided the preliminary identification of 28 phytocompounds. In addition, the compounds identified by GCMS were subjected to in silico molecular docking analysis in order to identify any interactions between the compounds and enzymes (α-amylase and α-glucosidase). After that, the best-docked compounds were subjected to ADMET studies which provide information on pharmacokinetics, drug-likeness, physicochemical properties, and toxicity. The present study highlighted that the ethanol extract of F. vasta has antidiabetic, antimicrobial, anti-viral, and anti-cancer potentials that can be further explored for novel drug development.